EFEKTIVITAS PELAKSANAAN SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG) DI BKD PROVINSI JAWA TENGAH - Astri Denaya; Titik Djumiarti (Journal of Public Policy and Management Review, 2018)
SIMPEG according to the decision of the Minister of the Interior No. 17 year 2000 is a management information system which functions to manipulate the data, management and administrative personnel in local government environment. SIMPEG is very important in providing services to all personnel, because the employees are an important asset in the conduct of the organization that must be well managed. Problems occurred in the input has not been able to manage the SIMPEG well, in operation less complete data to be processed, and the output data discrepancies in employees with facts. That assumption is caused by not effectively managing input and output operations. The purpose of this research is to know the effectiveness of the implementation of SIMPEG in BKD Central Java, as well as the factors that influence the effectiveness of the implementation of SIMPEG in BKD Central Java. A descriptive qualitative research methods, data analysis methods with domain according to Spradley. The results showed that the implementation of SIMPEG in BKD Central Java have not run effectively, viewed using the input indicator, operation and output. Factors that hinder the provision of SIMPEG, namely, human resources are limited, not all employees can operate the computer and the delay in the update of the data. The results of this research are recommended to provide the motivation of employees by means of enhancing training about SIMPEG so there is an increase in the employee master information technology